Construction and Application of a Flipped Classroom Model in Experimental Courses of Fundamentals of Nursing Based on University - Hospital Collaboration: A Case Study of Aseptic Technique - Zeng, Dandan; Nong, Huiling; Huang, Linyu; Huang, Xiaoyuan; Wei, Yongxian; Pan, Xinbai; Huang, Fangyan (Journal of Research in Vocational Education, 2025)
Objective: This study aimed to construct and validate a flipped classroom model (FCM) for experimental courses in Fundamentals of Nursing (FCM-FNPC) under university-hospital collaboration and evaluate its effectiveness using aseptic technique as an example. Through literature review, expert panel discussions, and three rounds of teaching seminars, a closed-loop teaching model was developed, comprising pre-class resources, in-class interactive activities, and post-class consolidation. Methods: A non-synchronous controlled trial was conducted, involving 2020-grade nursing undergraduates (control group, n=60) and 2021-grade students (experimental group, n=62) from Youjiang Medical University for Nationalities. Results: The control group received traditional instruction, while the experimental group adopted FCM-FNPC. Results: showed that the experimental group outperformed the control group in operational skills (89.5±4.2 vs. 82.1±5.6, P<0.01) and overall scores (85.3±3.8 vs. 78.9±4.5, P<0.05). Significant improvements were observed in collaborative skills (4.2±0.6 vs. 3.5±0.7) and information literacy (4.0±0.5 vs. 3.3±0.6) (P<0.05). Qualitative interviews revealed that students deepened their skill mastery through pre-class videos and in-class collaboration, while teachers reported enhanced teaching efficiency. Conclusion: This study confirms that FCM-FNPC effectively improves nursing experimental education and offers an innovative approach for skill-based courses like aseptic technique.